Isolation of myxobacteria with biological activities from the soil : Khóa luận tốt nghiệp Dược sĩ Đại học / Nguyen Le Bao Ngoc ; Nguyen Thi Ngoc Yen instructor - Nguyen, Le Bao Ngoc
Phụ lục: PL1 - PL6